ВОЗДЕЙСТВУЮЩИЙ ПОТЕНЦИАЛ ПАРЦЕЛЛЯЦИИ ВО ФРАНЦУЗСКИХ И РУССКИХ МЕДИАТЕКСТАХ / EFFECTING POTENTIAL OF PARCELING IN FRENCH AND RUSSIAN MEDIA TEXTS / POTENŢIALUL DECLANŞATOR AL PARCELĂRII ÎN TEXTELE MEDIA FRANŢUZEŞTI ŞI RUSEŞTI - Yuliya Bogoyavlenskaya (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2014)
Parceling is considered as a multifunctional phenomenon, a means having intellectual, emotional and esthetical influence upon the recipient. The specific character of this influence is studied in comparative aspect through French and Russian mass-media texts, where the parceling is an intentionally caused argumentative and rhetorical, figurative and expressive means. Parceling assures an adequate communicative and pragmatic reception of the text